(untitled) (Discussion Papers, 2012)
Centre for Regional Studies, Hungarian Academy of Sciences has organised the second East-Central European Regional Seminar - ECERS 2008 - in the city of Gyula, near the eastern border of Hungary. The aim of the seminar was to support the initiative of Warsaw Regional Forums and expand the XVIth Polish-Hungarian Geographical Seminar. This meeting aimed to highlight different aspects, spatial issues and problems of East-Central European borders, and the complexity of borderlands. There are twelve studies about different regional and geographical approaches reflecting innovative viewpoints. Most of the authors wrote about actual processes and conflicts of new spatial phenomena in EU countries, particulary crossborder-opportunities, features of peripheral areas, environmental and social problems. They pointed out new opportunities of spatial development next to the borderlands and the unique potentials of marginal areas. Some of the papers were based upon regional research and the others were case studies or summaries of different pilot projects. Most of the authors mentioned the importance of environmental, cultural, turistic and transport-functions of borders and the long term perspectives of these kind of areas were emphasised. The main conclusion of the conference was that the special geopolitical and geographical positions give advantages to these zones. Everybody agreed that - apart from the recent political paradigm - there is a need to create such a multifunctional areas which assures the local cohesion, economic and ecological sustainability for these borderlands. This sustainability must be based upon cooperation and partnership.